Nod proteins in mucosal defense against bacteria: implications for Crohn's disease - Girardin, Stephen (Henry Stewart Talks, 2011)
Innate immunity, Host detection of intracellular bacterial pathogens by Nod-like receptors, Dysregulation of intestinal immune control of bacteria, Crohn's disease